Westport [large type] - Comey, James, 1960- (Thorndike Press large print mystery series., 2024)
"It's been two years since Nora Carleton left the job she loved at the US Attorney's Office to become lead counsel at Saugatuck Associates, the world's largest hedge fund. Nora's new life falls apart when a coworker is murdered and she becomes the lead suspect. Nora calls in her old colleagues from the US Attorney's Office, Mafia investigator Benny Dugan and attorney Carmen Garcia. To clear Nora's name, Benny and Carmen hunt for the true killer's motive, but it seems nearly everyone at Saugatuck has secrets worth killing for. As Benny sets out ot interrogate her colleagues, Nora examines her histroy with the company to determine who set her up to take the fall"--